HUBUNGAN ANTARA MINAT BELAJAR PENDIDIKAN AGAMA ISLAM, PERSPEKTIF LINGKUNGAN SEKOLAH DAN KEDISIPLINAN BERIBADAH DI SMK MASMUR PEKANBARU: Minat Belajar PAI, Lingkungan Sekolah, Kedisiplinan Beribadah. - Rahman, Arini; Risnawati, Risnawati; Hamdani, M.Fikri (Kaisa: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to determine the relationship between interest in learning Islamic Religious Education (PAI), the perspective of the school environment, and the discipline of worship of students at SMK Masmur Pekanbaru. The background of this study is based on the importance of religious education and the support of the school environment in shaping students' religious character, especially in terms of discipline in worship. This research uses a quantitative approach with a correlation method. The population in this study was all students in grades X and XI of SMK Masmur Pekanbaru, with a sample of 40 respondents taken through the purposive sampling technique. The instrument used is a closed questionnaire with a Likert scale. Data analysis was carried out by partial correlation tests and multiple linear regression to determine the simultaneous and partial relationship between variables. The results showed that there was a positive and significant relationship between interest in learning PAI and the perspective of the school environment on the discipline of student worship. Interest in learning PAI and a conducive school environment jointly contribute to improving the discipline of worship among students. This finding confirms the important role of religious education and the school environment in shaping students' religious attitudes.